A Tauberian theorem for the power-series summability method - Çanak І.; Totur, Ü. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We introduce a one-sided Tauberian condition in terms of the weighted general control modulo oscillatory behavior of integer order m with m ≥ 1 for the power-series summability method.